ANALISIS KUALITAS PELAYANAN KESEHATAN DI INSTALASI RADIOLOGI RSUD SYEKH YUSUF KABUPATEN GOWA - Hasmawati Hasmawati; Najmi Kamariah; Alam Tauhid Syukur (Jurnal Administrasi Negara, 2018)
Abstract This research aims to find out the quality of health services in radiology department of Syekh Yusuf regional hospital in Gowa regency. The thinking model applied this study is the quality of health services which consist of five dimensions, namely reliability, responsiveness, assurance, empathy and physical evidence. The research method used is descriptive quantitative research. The techniques of data collection include questionnaires, interviews, observations, and document review of informants involving 92 patients, a frontline officer, three radiographers and one radiologist. The result shows that the quality of health services in the department of radiology of Syekh Yusuf regional hospital Gowa measured from the five dimensions as follows; The average score for reliability is 4.6; the average achievements for responsiveness and assurance are 4.52 and 4.53 respectively; the average score for empathy is 4.43; and the average score for the achievement of tangibility (physical evidence) is 4.65. Thus, the overall standard of health services in the department of radiology is considered qualified. Therefore, it is expected that the hospital and all the radiology staffs of Syekh Yusuf regional hospital in Gowa enhance the service quality. Keywords: Service Quality, Health services, Radiology